(untitled) (Research, Society and Development, 2022)
Objective: It consists of analyzing the scientific evidence in the literature about the importance of using auriculotherapy in terms of improving the symptoms of cancer patients. Methodology: This is an integrative review, carried out in 2022, between April and June. The Health Sciences Descriptors (DECs) used were “Auriculotherapy”, “Oncology Nursing” and “Complementary Therapies” combined with each other in the databases by the Boolean operator AND and OR. The Clinical Research Methodology (PICO) was used for the literature search and to select and evaluate the articles, the Preferred Report Items for Systematic Analysis and Meta-Analysis (PRISMA) strategy was used. In order to verify the level of evidence of the studies, the instrument recommended by Gershon and collaborators was used. Results and Discussion: After applying the eligibility criteria, four studies out of 45 were selected to compose the final sample. It was evidenced that auriculotherapy helps in the management of cancer impacts and has beneficial effects in cancer treatment. Conclusion: It is concluded with the analysis of the studies that auriculotherapy improves the quality of life of patients diagnosed with cancer.